2020
DOI: 10.1111/jar.12738
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive variables and offending behaviour in adults with intellectual disabilities: A systematic review

Abstract: BackgroundInterventions for offenders with intellectual disabilities (ID) have used cognitive variables as measures of treatment outcome. However, the relevance of cognitive variables to offending in people with intellectual disabilities is unclear. This review aimed to evaluate the evidence for a relationship between cognitive variables and offending in people with intellectual disabilities.MethodA systematic search identified studies comparing offenders and non‐offenders with intellectual disabilities on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Therefore, dysfunctional behavior, such as pre-occupation with sexual pedophilic themes, continuous consumption of child pornography, or even pedophilic reoffending, could possibly further negatively impact or strengthen this WM microstructure pattern. In contrast, lifestyle changes and psychotherapeutic interventions such as the BEDIT program ( 98 ), the Good Lives Model ( 95 ), or other types of psychosocial support could potentially lead to behavioral changes, which might eventually be reflected in changes in the WM microstructure pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dysfunctional behavior, such as pre-occupation with sexual pedophilic themes, continuous consumption of child pornography, or even pedophilic reoffending, could possibly further negatively impact or strengthen this WM microstructure pattern. In contrast, lifestyle changes and psychotherapeutic interventions such as the BEDIT program ( 98 ), the Good Lives Model ( 95 ), or other types of psychosocial support could potentially lead to behavioral changes, which might eventually be reflected in changes in the WM microstructure pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have further suggested individuals with intellectual disabilities have less empathy compared to people without intellectual disabilities (Bachara, 1976; Eyuboglu et al, 2018; Langdon et al, 2011). Again, the relationship between intellectual disabilities, empathy and sexual offending is complex with research producing inconsistent findings (Hammond & Beail, 2020). Offenders with intellectual disabilities (sexual and non‐sexual) have been shown to have lower empathy than non‐offenders with intellectual disabilities, offenders without intellectual disabilities and non‐offenders (Bachara, 1976; Langdon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%